Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Scramble Terhadap Hasil Belajar Siswa Pada Materi Hidrokarbon di Kelas X SMA Negeri 8 Palu - Suliadi, Ilham; Said, Irwan; Jura, Minarni Rama (Universitas Tadulako, 2017)
This study aimed to obtain description in application the cooperative learning model type scramble on student’s learning outcomes in hydrocarbon material in class X SMAN 8 Palu. This type of research was quasi-experimental research. This study was conducted at two group, 27 students in class XB as an experimental group and 28 students in class XA as a control group. The testing of student’s learning outcomes data used the statistical analysis t-test of the two parties with the prerequisite test: normality test and homogeneity test. The results of the data analysis, it was obtained the average values of students in experiment class () was 72.40 with a standard deviation of 11.86 and students in control class () was 67 with a standard deviation of 12.03. Based on the results of testing hypotheses by statistical t-test two parties, it was obtained –ttable<tcalculation> +ttable (tcalculation=2.37 and ttable=1.67) with a significance level α = 0.05 and degrees of freedom 53, then H0 was rejected and ha was accepted. It can be concluded that there is the effect of applying the cooperative learning model type scramble toward student’s learning outcomes in the hydrocarbon material in class X SMA 8 Palu.